Effect of feline skin specimen preparation on postexcision and postfixation tissue shrinkage. Issue 12 (December 2016) - Risselada, Marije; Mathews, Kyle G; Griffith, Emily
Objectives: This study was performed to assess skin–muscle–fascia specimen shrinkage and donor site changes, and to compare three techniques of specimen preparation for their effect on specimen shrinkage postexcision and after formalin fixation in feline cadaveric specimens. Methods: Fifteen fresh feline cadavers were used for this study. Gelatin spheres were implanted in paired thoracic subcutaneous pockets and subsequently excised with 30 mm lateral margins and a fascial plane as the deep margin. Skin and fascia were either left unsutured, sutured together using four simple interrupted quadrant sutures ('four-quadrant-sutured') or sutured together in a continuous pattern ('circumferentially sutured'). Specimens were measured for tumor-free margins on the excised and fixed specimens. The donor site defect was assessed for enlargement after specimen excision. Statistical analyses were performed to assess the donor site enlargement, and the influence of preparation technique on margin size, with significance set at P <0.05. Results: The closest skin margins on the excised and fixed specimens were significantly smaller than the planned 30 mm margins; however, no significant difference was found between postexcision and postfixation specimens. No significant differences were found between the three techniques ( P = 0.74) with regard to margins either after excision or fixation. The fascial and skin defects of the donor site were significantly larger than the planned excision. Conclusions and relevance: Surgically obtained feline skin–muscle–fascia specimens will significantly decrease in size prior to formalin fixation, resulting in falsely decreased measurements from tumor to tissue margins. Affixing the skin to the fascia does not significantly influence this decrease in margin size in feline tissue specimens at this location.